Comparison of the library Information System Implementation based on Artificial Intelligence at the Universitas Pendidikan Indonesia (UPI) and UIN Syarif Hidayatullah Jakarta - Harahap, Fatika Salsabila; Ramadhan, Indriani; Suhailah, Siva Cahaya; Dewiyana , Himma (Jurnal Tadwin, 2025)
The rapid development of digital technology, especially artificial intelligence (AI), has fundamentally transformed higher education services, including the management of academic information through libraries in the Industry 4.0 era. Educational institutions are urged to be adaptive, innovative, and smart technology-based. This study aims to conduct an in-depth comparative analysis of AI-based library information system implementation at Universitas Pendidikan Indonesia (UPI) and Universitas Islam Negeri Syarif Hidayatullah Jakarta (UIN Jakarta). A descriptive qualitative approach was employed, collecting data through literature review, system documentation, and contextual observation to understand the phenomenon comprehensively. Research findings indicate that both institutions have implemented various AI features, including information service chatbots, user-preference-based collection recommendation systems, and automated document classification. UPI stands out with a strategic focus on personalization and user experience through digital innovation policies, while UIN Jakarta prioritizes operational efficiency and extended access via cross-unit collaboration and integration with popular communication applications. AI implementation demonstrably enhances service efficiency and responsiveness, simultaneously increasing user satisfaction. However, challenges such as uneven digital literacy and limited human resource capacity remain concerns. This research benefits by enriching the literature on higher education digitalization, providing practical recommendations for developing contextual AI library systems, and contributing to the adaptive smart campus vision.